Widespread brain transcriptome alterations underlie the neuroprotective actions of dietary saffron. Issue 5 (21st October 2016) - Skladnev, Nicholas V.; Ganeshan, Varshika; Kim, Ji Yeon; Burton, Thomas J.; Mitrofanis, John; Stone, Jonathan; Johnstone, Daniel M.
Abstract : We confirm previous reports that pre‐conditioning by saffron consumption protects the brain of mice against parkinsonian MPTP insult. Intriguingly, 5 days of saffron pre‐conditioning provided more robust neuroprotection than 10 days. Investigation of how saffron consumption influences the brain transcriptome revealed molecular changes consistent with neuroprotection as well as the up‐regulation of some specific stress‐inducible systems. These findings raise the possibility that saffron, like other phytochemicals, may act by inducing an adaptive stress response. Abstract: Dietary saffron has shown promise as a neuroprotective intervention in clinical trials of retinal degeneration and dementia and in animal models of multiple CNS disorders, including Parkinson's disease. This therapeutic potential makes it important to define the relationship between dose and protection and the mechanisms involved. To explore these two issues, mice were pre‐conditioned by providing an aqueous extract of saffron (0.01% w/v) as their drinking water for 2, 5 or 10 days before administration of the parkinsonian neurotoxin MPTP (50 mg/kg). Five days of saffron pre‐conditioning provided the greatest benefit against MPTP‐induced neuropathology, significantly mitigating both loss of functional dopaminergic cells in the substantia nigra pars compacta ( p  <   0.01) and abnormal neuronal activity in the caudate‐putamen complex ( p  <   0.0001). RNA microarray analysis of the brain transcriptome of mice pre‐conditioned with saffron for 5 days revealed differential expression of 424 genes. Bioinformatics analysis identified enrichment of molecular pathways (e.g. adherens junction, TNFR1 and Fas signaling) and expression changes in candidate genes ( Cyr61, Gpx8, Ndufs4, and Nos1ap ) with known neuroprotective actions. The apparent biphasic nature of the dose–response relationship between saffron and measures of neuroprotection, together with the stress‐inducible nature of many of the up‐regulated genes and pathways, lend credence to the idea that saffron, like various other phytochemicals, is a hormetic stimulus, with functions beyond its strong antioxidant capacity. These findings provide impetus for a more comprehensive evaluation of saffron as a neuroprotective intervention.